Quantifying wave attenuation by seagrass: a comprehensive review of assessment techniques - Xu, Xihang; Salauddin, M. (Frontiers in Marine Science, 2025)
Seagrasses, often referred to as ecosystem engineers, play a vital role in shallow coastal waters worldwide. They can not only provide key ecological benefits such as ecosystem restoration and carbon sequestration, but also offer significant engineering benefits, including sediment stabilization and wave energy dissipation. Despite its potential biological benefits, the mechanisms behind seagrass-induced wave attenuation remain inadequately understood. Furthermore, inconsistencies in the recorded metrics complicate the comparison of findings across various experimental studies. This study aims to address these challenges by thoroughly examining six key parameters for assessing the wave attenuation performance of seagrass meadows: wave energy dissipation, drag coefficient, wave transmission coefficient, wave attenuation coefficient, wave-induced flow velocity, and turbulent kinetic energy. By systematically reviewing the most relevant lab-based experimental studies conducted from 2000 to 2024, this study summarises the developments, applications, and performance of these key parameters in analysing seagrass-induced wave dissipation, discussing the physical mechanism behind. The effects of currents on seagrass-induced wave attenuation performance are also investigated. The findings of this work provide a foundation for conducting a unified framework to assess the impact of canopy features and wave characteristics on seagrass-induced wave attenuation, further contributing to the development of coastal protection policies in combination with seagrass restoration guidance.